How does altruistic leader behavior foster radical innovation? The mediating effect of organizational learning capability. Issue 8 (7th November 2016) - Domínguez Escrig, Emilio; Mallén Broch, Francisco Fermín; Chiva Gómez, Ricardo; Lapiedra Alcamí, Rafael
Abstract : Purpose: The purpose of this paper is to provide empirical evidence of the relationship between altruistic leader behavior and radical innovation, using organizational learning as an explanatory variable. Design/methodology/approach: To confirm the hypotheses, structural equations were used on a data set from a survey carried out on Spanish firms with recognized excellence in human resources management. Findings: The study empirically validates the conceptual model. Results suggest that organizational learning capability fully mediates the relationship between altruistic leader behavior and radical innovation. Research limitations/implications: The database used in the study is very heterogeneous. Future research might delimit the database by organization size or sector. Practical implications: Results suggest ideas for organizations that want to implement a working environment that fosters innovation performance in order to achieve radical innovations. Originality/value: This is one of the few studies to concentrate on altruistic leader behaviors as such. This paper contributes to understanding how altruistic leader behavior affects radical innovation and the key role played by organizational learning capability.